Comparative Effects of the Numbered Heads Together and Two Stay Two Stray Models on Higher-Order Thinking Skills: The Moderating Role of Adversity Quotient in Learning Number Patterns - Nurditasari, Intan; Siswanto, Siswanto; Nurhasanah, Farida (EDUPEDIA Publisher, 2026)
Purpose – This study aims to examine the comparative effectiveness of Numbered Heads Together (NHT) and Two Stay Two Stray (TSTS) cooperative learning models on students' Higher-Order Thinking Skills (HOTS), investigate the influence of Adversity Quotient (AQ) types (Climbers, Campers, Quitters), and explore the interaction effect between learning models and AQ on HOTS. Methodology – This research employed a quasi-experimental 3x2 factorial design with stratified cluster random sampling among 8th-grade students in junior high schools. Data were collected through HOTS tests and AQ questionnaires and analyzed using two-way ANOVA. Findings – The statistical analysis revealed no significant main effect regarding the effectiveness of the NHT versus TSTS models on HOTS overall. However, a significant interaction was found between the learning models and students' Adversity Quotient (AQ). Specifically, the findings indicate that the NHT model is more effective for students with higher resilience (Climbers and Campers), whereas the TSTS model offers greater benefits for students with lower resilience (Quitters). This demonstrates that the effectiveness of cooperative learning strategies on HOTS is moderated by students' psychological resilience profiles. Novelty – This study uniquely integrates cooperative learning models with students' psychological resilience levels, offering insights into differentiated instructional strategies tailored to learners' AQ profiles. Significance – This study provides practical benefits for educators and curriculum designers in selecting learning models that align with students' psychological characteristics to optimize HOTS. The findings are also significant for school counselors in developing intervention programs to enhance students' learning resilience.